Współpraca rodziny i szkoły w wychowaniu spółdzielczym dzieci i młodzieży w Drugiej Rzeczypospolitej (1918-1939) - Magiera, Elżbieta (Karkonoska Państwowa Szkoła Wyższa, 2011)
Pedagogical journalism and literature of the interwar period emphasised importance of the cooperation between family and school with respect to cooperative education of school-age children and youth. Cooperative education started usually in family through the formation of reason, will and emotions. Family home constituted a basic level of education and could repeatedly stimulate cooperative interests. Common work of the family at family farm or in craft or cottage industry business became the first school of cooperation and joint-action on which cooperative activity was based. Family home played a supporting part in the development of student cooperative. The acceptance of parents and their recognition, and sometimes their involvement in the work of student cooperation, were a form of encouragement for students and teachers for further activity of the cooperative. At the same time, student cooperative - in particular in rural areas - was a medium stimulating the parents of these students and the environment to cooperatistic actions. The social life of school was guided by the principle of convergence, i.e. its interpenetration and complementation by the family home and environment life. The idea of cooperation in the interwar educational systembeing accomplished in practice by means of student cooperatives had the possibilities ofplaying a very big part. This was determined by its broad application in educational activity of the Polish school as well as its understanding and acceptance by the family and environment.Important part was played by the tutor of student cooperative. His / her duty was to tighten the cooperation between student cooperative and family homewhich, on the one hand, ensured the understanding of teacher's actions and, on the other hand, provided material and moral assistance for the cooperative. At the same time, teacher - through student cooperative - could influence socially and educationally the family and environment, showing the benefits yielding from mutual cooperative work based on joint-action.
Keywords: rodzina; szkoła; wychowanie; dzieci; młodzież; Druga Rzeczpospolita